A new species of Anteon from Zimbabwe (Hymenoptera, Dryinidae) - Olmi, Massimo; Capradossi, Leonardo; Guglielmino, Adalgisa (Zootaxa, 2021)
A new species from Zimbabwe, Anteon chirindense sp. nov. (Hymenoptera: Dryinidae: Anteoninae), is described and illustrated. Its relationship with other Afrotropical species of Anteon is discussed. The new species is close to A. haladai Olmi, described from Zambia, but its chela is different with inner margin of protarsomere 5 curved, whereas it is almost rectilinear in A. haladai. The key to the Afrotropical species of Anteon is modified to include the new species.